THE REALITY OF GROSS DOMESTIC PRODUCT IN THE FINANCIAL SHOCKS CASE STUDY OF IRAQ FOR THE PERIOD (2004-2019) - Abdul Rahman Karim Abdul Ridha (Scholar Express Journals, 2023)
The study dealt with the relationship between fiscal policy shocks and GDP results in Iraq for the period 2004-2019 . During the duration of the study, it was found that there is a positive relationship between financial shocks and gross domestic results. The expansion and increase in government spending financed by the increase in government revenue has increased GDP and vice versa in the event of negative financial shocks. Certainly, a rentier country like Iraq that relies heavily on oil revenues will be vulnerable to expansionary and deflationary financial shocks due to the fluctuation of those revenues that play their role in transferring these shocks to GDP. Therefore, it can be said that Iraq has adopted and continues to rely on wrong financial policies in the administration of the state, especially when continuing to rely on oil revenues, which provided the safe road even in the most severe circumstances, especially those that were the product of wars and the prevalence of financial and administrative corruption. This was reflected in the gross domestic product, which witnessed a clear fluctuation due to the circumstances experienced by Iraq, and that this fluctuation in the size of the output is doomed to fluctuation in oil revenues dependent on its international prices and the quantities produced. This was reflected in the weakness of the economic structure, which lacks diversification of sources of income and the low contribution of the service and distribution sectors to the formation of GDP. Thus, it is necessary to diversify the economic base in order to form various sources of financing for the government budget by working to increase the contribution of non-oil sectors to the GDP such as agriculture, industry, tourism and others, especially after the repeated shocks that hit global oil prices. It is also necessary to diversify the structure of government revenues in order to protect the government budget from sudden or large fluctuations in oil revenue
Keywords: The financial shocks; the gross domestic product; the Economics; Iraq